Studi Daya Dukung Ekowisata Air Terjun Begiham di Kabupaten Sanggau Kalimantan Barat: Carryng Capacity Studies of Ecotourism Begiham Waterfall In Sanggau Distric West Kalimantan - Yunita Kristin; Adijaya, Mardan; Wira Hadinata, Fitra (Universitas Muhammadiyah Malang, 2024)
This research was carried out from May -July 2022, using a survey method and descriptive analysis of the Tourism Suitability Index (IKW) analysis. Primary data was collected by direct measurement as well as interviews and filling out questionnaires. Activities that can be done in this area include playing in the water, looking at the scenery and camping. The magnitude of the value of the Begiham waterfall tourism suitability index, is the activity of playing in water the IKW value of 2.86 means that tourism is very suitable for sitting and activities seeing the sights with an IKW value of 2.22 means that tourism suitability is appropriate and camping activities with an IKW value of 2.2 means that tourism suitability is appropriate.While the value of the Area Carrying Capacity in the Begiham waterfall is 115 people/day for playing in the water, seeing the sights and camping. Begiham waterfall is very suitable for ecotourism purposes with a carrying capacity that is still being developed further, in this area you can do camping activities and enjoy the wild nature.